PERSONALITY PSYCHOLOGY AND ITS METHODOLOGICAL FOUNDATIONS (Web of Teachers: Inderscience Research, 2026)
Personality psychology is a fundamental branch of psychology that focuses on the comprehensive study of individuals’ patterns of thinking, feeling, and behaving. This field examines the unique characteristics and internal processes that differentiate one person from another, explores how personality develops and changes throughout the life span, and delves into how personality influences interactions with the environment and society. The methodological foundations of personality psychology are diverse and based on interdisciplinary approaches, connecting philosophy, biology, sociology, and other related sciences to develop a scientific understanding of individual differences.